Bacillus species at the Canberra Airport: A comparison of real-time polymerase chain reaction and massively parallel sequencing for identification. (February 2019) - Gahan, M.E.; Bowman, S.; Chevalier, R.; Rossi, R.; Nelson, M.; Roffey, P.; Xu, B.; Power, D.; McNevin, D.
Highlights: Consistency between two MPS approaches and between MPS and qPCR. Greater detection of Bacillus at the Canberra Airport with MPS compared to qPCR. Selected MPS target(s) generated metagenomic fingerprint of bacterial community. Selected MPS target(s) could not resolve Bacillus beyond the B. cereus group. Choice of target(s) is key to differentiate pathogenic from non-pathogenic species. Abstract: Anthrax, caused by the Gram-positive, spore forming bacterium Bacillus anthracis, is a disease with naturally occurring outbreaks in many parts of the world, primarily in domestic and wild herbivores. Due to the movement of people and stock, B. anthracis could, however, be at transportation hubs including airports. The continuous threat to national and international security from a biological agent release, or hoax attack, is a very real concern. Sensitive, robust and rapid (hours-day) methods to identify biological agents, including B. anthracis, and distinguish pathogenic from non-pathogenic species, is an essential cornerstone to national security. The aim of this project was to determine the presence of Bacillus species at the Canberra Airport using two massively parallel sequencing (MPS) approaches and compare with previous results using real-time polymerase chain reaction (qPCR). Samples were collected daily for seven days each month from August 2011–July 2012 targeting movement of people, luggage and freight into and out of the Canberra Airport. Extracted DNA was analysed using qPCR specific for B. anthracis . A subset of samples was analysed using two MPS approaches. Approach one, using the Ion PGM™ (Thermo Fisher Scientific; TFS) and an in-house assay, targeted the two B. anthracis virulence plasmids ( cya and capB genes) and a single conserved region of the 16S rRNA gene. Approach two, using the Ion S5™ (TFS) and the commercial Ion 16S™ Metagenomics Kit (TFS), targeted multiple regions within the bacterial 16S rRNA gene. Overall there was consistency between the two MPS approaches and between MPS and qPCR, however, MPS was more sensitive, particularly for plasmid detection. Whilst the broad-range 16S genomic target(s) used in both MPS approaches in this study was able to generate a metagenomic fingerprint of the bacterial community at the Canberra Airport, it could not resolve Bacillus species beyond the level of the Bacillus cereus group. The inclusion of B. anthracis virulence plasmid targets in the in-house assay did allow for the potential presumptive identifications of pathogenic species. No plasmid targets were in the Ion 16S™ Metagenomics Kit. This study shows the choice of target(s) is key in MPS assay development and should be carefully considered to ensure the assay is fit for purpose, whether as an initial screening (presumptive) or a more specific (but not entirely confirmatory) test. Identification approaches may also benefit from a combination of MPS and qPCR as each has benefits and limitations.